Valuation of Telus corporation - Friedel, Jaromír (2019)
The thesis aims to provide valuation of Telus Corporation (TELUS) for a hypothetical marginal investor as of 1/1/2019. TELUS is a Canadian national telecommunications company listed at the Toronto Stock Exchange. Strategic and financial analysis conducted prior to the valuation unveiled that TELUS is a company with substantial competitive advantage and strong positive outlook. In addition, market development and company revenues were modelled in the strategic analysis. Subsequently, development of the key value drivers consisting of operating margin, working capital and capital expenditures was projected. Cost of equity was estimated using forward looking equity premiums and bottom up Beta methodology. Cost of equity together with cost of debt yielded WACC of 5.38%. TELUS was valued using DCF Entity method, which yielded value of CAD 49.97 per share. DCF valuation was supplemented by relative valuation using adjusted EV/EBITDA multiple which yielded price of CAD 43.63 per share. Value of CAD 49.97 from DCF valuation was accepted as final value recommendation. With stock price of CAD 45.25, TELUS was undervalued as of 1/1/2019 according to the DCF valuation.